التأثير التثبيطي لبعض نباتات العائلة المركبة Composite في نمو فطر Erysiphe graminis f.sp. tritici L. المعزول من اوراق نبات الحنطة Triticum aestivum L. وانبات ابواغه - راضي حيدر (University of Thi-Qar Journal of Science, 2008)
This study aimed to examine the activity of aqueaos extract of Helianthus annuus L. , Tagetes patula L. and Artemisia herba_alba L. on spore germination and the growth of Erysiphe graminis f.sp. tritici that isolated from Triticum aestivum L. The results showed that the aqueaos extract of Helianthus annuus L., Tagetes patula L. and Artemisia herba_alba L. were differed significantly reduced the growth and spore germination of Erysiphe graminis f.sp. tritici , The higher concentration (15%) of all extracts revealed greater inhibition to the fungal growth. Artemisia herba_alba and Tagetes patula aqueaos extracts had a lower and higher percentage of the growth of Erysiphe graminis f.sp. tritic ,were (42.1% ,77.3%) consecutively. Artemisia herba_alba had a lower percentage of the spore germination of Erysiphe graminis f.sp. tritici was (31.1%) , and Helianthus annuus had higher percentage was (71.2% ). The aim of this study is to find out the chemical compound of aqueaos extract of Helianthus annuus L. , Tagetes patula L. and Artemisia herba_alba L. to contain several compound have antifungal activity , It Flavonoids ,Alkaloids and Saponins.